Hubungan antara Endurance Sport Self Efficacy dengan Peak Performance pada Atlet Sepak Bola PPOP DKI Jakarta - Faiz Pramadhan; Vinaya Untoro; Andri Setia Dharma (Jurnal Ilmiah Psikologi MIND SET, 2022)
Football is one of the most popular endurance sports in Indonesia. The high interest of the Indonesian people to become soccer athletes presents the opportunity to become athletes by joining soccer clubs to training centers to become professional players, one of which is at PPOP DKI. This study aims to examine the relationship between endurance sport self-efficacy and peak performance in soccer athletes of PPOP DKI Jakarta. The participants in this study are 43 PPOP athletes in DKI Jakarta using the total population sampling technique. The measuring instruments used in this study are the Peak Performance Instrument from Maheswari (2018) and the Endurance Sport Self-Efficacy Scale (ESSES) from Anstiss et al. (2018). The results of data analysis using pearson product moment showed that there was a significant relationship between peak performance and endurance sport self-efficacy in soccer athletes of PPOP DKI Jakarta.